MASS RAPID TRANSIT (MRT) DEMAND AND CAPACITY ASSESSMENT FOR RAIL TRANSPORT IN MALAYSIA - Syamsunur, Deprizon; Xiang, Jason Ong Jin; binti Suro, Salihah; Chek, Moon Wei; Retno, Deddy Purnomo; Nelfia, Lisa Oksri; Bt Md Noh, Nur Ilya Farhana; Ng, Jing Lin Ng (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2024)
Assessing the quality of MRT services unveils a generally satisfactory experience among respondents, with comfort emerging as a particularly noteworthy aspect. Satisfaction levels for MRT service quality range from 3.63 to 4.12, indicating a favorable perception overall. Notably, comfort stands out with the highest satisfaction rating, surpassing the "Satisfied" threshold, while accessibility receives the lowest rating. In essence, the majority of MRT passengers’ express contentment with the service, spanning operation, maintenance, and performance. Additionally, Bukit Bintang station emerges as a focal point during peak hours due to its proximity to diverse amenities. However, the prevalence of respondents underscores the necessity for broader demographic representation in future studies. Anticipated increases in MRT ridership necessitate proactive measures to accommodate the growing demand, with projected passenger numbers expected to rise significantly. Peak demand for the MRT SBK line is estimated at 115,498.543 passengers per day, reflecting a notable escalation of 281.82% across various purposes. Yet, reliance on responses may introduce biases in trip generation models and subsequent travel demand forecasting, emphasizing the importance of diversifying the respondent pool for more accurate predictions. Overall, the evaluation underscores the satisfactory nature of MRT services, particularly in terms of passenger comfort.